Attitudinal Loyalty Towards Online Stores Between Loyal and Disloyal Clients: Differences Across Four Countries - Vytautas Dikcius; Karina Adomaviciute - Sakalauske; Neringa Vilkaite - Vaitone; Sigita Kirse (Organizations and Markets in Emerging Economies)
The concept of loyalty has remained a central theme in business for over 50 years. This concept has gained additional attention with the growth of online retailing due to rapidly changing retail environments. Numerous studies have focused on the a ntecedents of online store loyalty; however, unlike previous works, the present study explores a conceptual perception of loyalty. This study provides insights into behavioral and attitudinal perspectives and concentrates on the importance of the affective dimension of attitudinal loyalty. Additionally, this study analyzes differences in attitudinal loyalty toward online stores between loyal and disloyal respondents. The study was based on a survey performed in four countries—the USA, China, Spain, and Lithuania. The results highlight the importance of the affective aspect of loyalty and differences in its evaluation among the surveyed countries. The findings reveal significant and stable differences in perception of the three dimensions of attitudinal loyalty between loyal and disloyal respondents; however, in contrast to expectations, the disloyal respondents exhibited very high levels of attitudinal loyalty. These findings contribute to better measurement and interpretation of loyalty for both scientific studies and business practitioners.